KEANEKARAGAMAN SEMUT (HYMENOPTERA: FORMICIDAE) PADA KAWASAN PENYANGGA DI PERKEBUNAN KELAPA SAWIT KILIRAN JAO KECAMATAN KAMANG BARU KABUPATEN SIJUNJUNG - Suryayulni, Nila - (Pendidikan Biologi, 2014)
A study about ants diversity at a buffer zone area of palm oil (Elaeis guineensiis Jacq.) plantation of PT. BinaPratama Sakato Jaya (BPSJ) Kiliran Jao Sijunjung District West Sumatera, by using âQuadra Protocolâ (FreeCollection, Honey Bait, Leaf Litter Sampling, and Soil Core Sampling) methods was conducted on June 2014.A total of 22 species, that belongging to 7 subfamillies, 14 tribe, 19 genera and 171 individual of ants wascollected. The diversity index of ants in this study was 2, 39. The highest number of species was found inFormicinae (8 species) and the lowest one was found in Aenictinae, Dorylinae and Pseudomyrmicinae (onespecies respectively). Polyrachis was found as a genus the highest number of species (4 species).